ANALISIS KEMAMPUAN GURU SEKOLAHDASAR DALAM MEMAHAMI KONSEP PENGGUNAAN TANDA BACA SE-KECAMATANTAMPAN PEKANBARU - Otang Kurniaman; Eddy Noviana; Muhamad Nukman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
This reseach form is survey reseach which is done to see the teachers‟ ability inunderstanding punctuation.Tecniques in getting data is that 30 valid questions are given to theteachers. The samples in this reseach are 81 teachers in Tampan district with the level ofprecision 10%. the teachers‟s ability in Tampan district were analyzedbased on category.Among 81 teachers 1 teacher (1,23%) gotthe best category, 31 teachers (38,27%) gotgood,38teachers (46,91) gotfair category , and 11 teachers (13,58) gets less category. Those resultswere got from the test that was given to the primary school teachers in Tampan district. Theaverage score is 63,5 with fair category.This shows that primary school teachers did not passbased on classical completeness 39,50% then it seems that the teachers‟ ability is still low.keyword : punctuation